Iot-Based Blood Pressure and Body Temperature Monitoring System - Saputro, Guruh Eko; Yohandri, Y; Mairizwan, M; Yuniarti, Elsa (Department of Physics – Universitas Negeri Padang UNP, 2022)
Health is an essential element that humans must consider. Examination of vital signs has two critical parameters in the diagnosis: blood pressure and body temperature. Blood pressure is a critical factor for the circulatory system. There are two types of blood pressure, namely systolic and diastolic. Body temperature is a measured body temperature expressed in degrees Celsius (℃). We developed an IoT-based blood pressure and body temperature monitoring device using MPX5100DP & DS18B20 sensors. The measurement carried out by comparing pressure and temperature data with standard tool, it was found that the percentage level of accuracy of the average pressure of 96.26% and temperature of 98.61%. Accuracy data were obtained for pressure measurement is 93.01% and for temperature measurement is 99.91%. The error on the device are found to be 2.96% systolic pressure, 3.29% diastolic pressure, and 0.63% body temperature. According to that, developed blood pressure and body temperature monitoring tool can work satisfiedly